Signifikansi Larangan Operasi Plastik Dalam Penafsiran QS. An Nisa (4): 119 Perspektif Makna Cum Maghza - Azizah Kumalasari (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2020)
This article tries to find out the significance of the plastic surgery ban in Qs. An Nisa (4): 119. As this proposition is used to legitimize the practice of plastic surgery in the Qur’an prespective, on the other hand, its axinstence is increasingly becoming a trend among the public, which is known as cosmetic surgery. So that there is no commond ground between the morals in the Qur’an with all the interpretations and the phenomenon of cosmetic surgery. The author uses a thematic-analysis method with the theory of hermeneutic Makna cum maghza with an emphasis on the discussion of the sentence being examined for its meaning and a review of the macro and micro of its asbabun nuzul when the verse is reveealed. So that from reading both of them can take the significance or the main massage from Qs. An Nisa (4): 119. The results of the discussion this verse puts forard the benefit of the whole people, with several limitation that need to be considered when doing plastic surgery. Such as; as needed, does not change the function of the operated organs and does not harm others in the practice of organ transplantation.